Deciphering the past to inform the future: preparing for the next ("really big") extreme event. Issue 7 (6th April 2020) - Peters, Debra PC; Burruss, N Dylan; Okin, Gregory S; Hatfield, Jerry L; Scroggs, Stacey LP; Huang, Haitao; Brungard, Colby W; Yao, Jin
Abstract : Climate change will bring more extremes in temperature and precipitation that will impact productivity and ecosystem resilience throughout agroecosystems worldwide. Historical events can be used to identify drivers that impact future events. A catastrophic drought in the US in the 1930s resulted in an abrupt boundary between areas severely impacted by the Dust Bowl and areas that were less severely affected. Historical primary production data confirmed the location of this boundary at the border between two states (Nebraska and Iowa). Local drivers of weather and soils explained production responses across the boundary before and after the drought (1926–1948). During the drought, however, features at the landscape scale (soil properties and wind velocities) and regional scale (the Missouri River, its floodplain, and the nearby Loess Hills) explained most of the observed variance in primary production. The impact of future extreme events may be affected by land surface properties that either accentuate or ameliorate the effects of these events. Consideration of large‐scale geomorphic processes may be necessary to interpret and manage for catastrophic events.